أساليب التنبؤ بالفشل المالي وأهميتها في ضمان إستمرارية المؤسسة الإقتصادية - محمد الأمين بوخيط (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2024)
ملخص تهدف هذه الدراسة إلى معرفة مدى مساهمة أساليب التنبؤ بالفشل المالي في ضمان استمرارية المؤسسات الصغيرة والمتوسطة الجزائرية، ومقدرتها على التنبؤ بالفشل المالي قبل وقوعه، واتاحة الفرصة والوقت اللازمين للمسؤولين على هذه المؤسسات من أجل اتخاذ الإجراءات التصحيحية التي تمنع المؤسسة من الوقوع في الإفلاس والتوقف عن النشاط. حيث احتوت هذه الدراسة في جانبها النظري على فصل جمع مختلف المفاهيم النظرية المتعلقة بالمعلومة المالية والفشل المالي والتنبؤ بالفشل، كما تم تناول قضية استمرارية المؤسسة الاقتصادية والتعامل مع المخاطر التي تواجهها، مع الإشارة إلى أساليب التنبؤ بالفشل المالي على اختلاف أشكالها، ثم تلا ذلك تطبيق بعض الأساليب المختارة على عينة من المؤسسات الصغيرة والمتوسطة في الجانب التطبيقي من الدراسة. و قد خلصنا في هذه الدراسة إلى اختلاف شاسع في نتائج التنبؤ باختلاف الأسلوب المتبع، إلا أن نموذج ألتمان للأسواق الناشئة كان أفضل النماذج أداء وموافقة لطبيعة المؤسسات الصغيرة والمتوسطة الجزائرية، كما سجلنا تأثرا لدقة النموذج باختلاف حجم المؤسسة وقطاع النشاط. الكلمات الدالة: استمرارية المؤسسة الاقتصادية، التنبؤ بالفشل المالي، المؤسسات الصغيرة والمتوسطةsummary This study aims to find out the extent to which financial failure prediction methods contribute to ensuring the continuity of Algerian small and medium enterprises, and their ability to predict financial failure before it occurs, and to provide the necessary opportunity and time for those in charge of these enterprises in order to take corrective measures that prevent the enterprise from falling into bankruptcy and ceasing activity. . This study, in its theoretical part, contained a chapter on collecting various theoretical concepts related to financial information, financial failure, and predicting failure. The issue of the continuity of the economic enterprise and dealing with the risks it faces was also dealt with, in addition to the indication of the methods of predicting financial failure in all its forms. Then, some applications followed. The selected methods on a sample of small and medium enterprises in the applied side of the study. In this study, we concluded a wide difference in the prediction results according to the method used, but the Altman model for emerging markets was the best performing model and in agreement with the nature of Algerian small and medium enterprises, and we also recorded that the accuracy of the model was affected by the size of the enterprise and the sector of activity. Key words: Continuity of the economic enterprise, prediction of financial failure, small and medium enterprises
دراسة حالة
Keywords: إستمرارية المؤسسة الإقتصادية; التنبؤ بالفشل المالي; المؤسسات الصغيرة; أساليب التنبؤ بالفشل المالي